2015
DOI: 10.18517/ijaseit.5.4.537
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Methyl Gallate Isolated from the Leaves of Toona sureni

Abstract: The phenolic compound has been isolated from the leaves of Toona sureni (Blume) Merr and evaluated against 3 microorganisms, including gram-positive and gram-negative bacteria. The structure was determined to be methyl 3,4,5trihydroxybenzoate (methyl gallate), based on UV-vis, FTIR, NMR and MS spectra. The antibacterial activity of the compound was evaluated using an impregnated paper disk method and compared with that of chloramphenicol. It was effective on the inactivation of Escherichia coli , Staphylococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 5 publications
2
8
0
2
Order By: Relevance
“…MIC and MBC values of methyl gallate were 50 and 100 µg/mL respectively as shown in Tables 2 and 3. This result is in line with a previous study on antimicrobial activity of methyl gallate isolated from Toona sureni 9 and Anacardium accidentale L.…”
supporting
confidence: 93%
“…MIC and MBC values of methyl gallate were 50 and 100 µg/mL respectively as shown in Tables 2 and 3. This result is in line with a previous study on antimicrobial activity of methyl gallate isolated from Toona sureni 9 and Anacardium accidentale L.…”
supporting
confidence: 93%
“…These results agree with the findings reported by Choi et al, they mentioned that methyl gallate, as a major component of Galla rhois, exhibited strong antimicrobial activity against E. coli [34]. Moreover, Ekaprasada et al showed that 10 mg/l of methyl gallate isolated from the leaves of Toona sureni showed antibacterial activities against each of Bacillus subtilis, Staphylococcus aureus and E. coli with inhibition zones equal 8, 10 and 8 mm, respectively [30]. Phenolic compounds are thought to inhibit microbial enzymes possibly through reaction with sulfhydryl groups (the oxidized phenols) or through nonspecific interactions with the proteins [35].…”
Section: Resultssupporting
confidence: 91%
“…It was previously isolated from plants showing medicinal properties, e.g. Toona sureni [30] and Spondias pinnata [31]. Also, it was identified and isolated from the filtrate of the fungus Penicillium janthinellum [16].…”
Section: Resultsmentioning
confidence: 99%
“…Crude extracts upon evaluation of antioxidant activity using DPPH and ABTS method showed IC 50 value ranging from 100-150 μgml -1 and 80-150 μgml -1 respectively with different test solvent extracts. Earlier report of antioxidant compound has been well described with potent DPPH activity resulting IC 50 value 1.02 μgml -1 (Ekaprasada et al 2009). …”
Section: Resultsmentioning
confidence: 93%